Alla älskar en underdog: Strategiskt berättande i bokbranschen - Nauwerck, Malin (Tidskrift för litteraturvetenskap, 2015)
Everyone Loves the Underdog – Corporate Storytelling in the Business of Books This article discusses the book business’ tradition of anecdotes and tale-telling in relation to a newer trend of corporate storytelling. Taking the example of Scots publishing house Canongate Books and its figurehead, star publisher Jamie Byng, as a starting point for discussion, I show how publishing houses can build publishing profiles/brand themselves with storytelling, and how, in this process, recurring narrative tropes and clichés are consciously linked to cultural values. This practise – comparable to the marketing strategies used by companies such as Swedish hamburger franchise MAX – is then used, I argue, by independent publishers to position themselves in a literary field characterised by increased polarisation.